1996
DOI: 10.2135/cropsci1996.0011183x003600050048x
|View full text |Cite
|
Sign up to set email alerts
|

AFLP Analysis of Gene Pools of a Wild Bean Core Collection

Abstract: Studies of diversity permit conclusions about the genetic structure of species. Systematically developed core collections are a particularly good tool for such purposes. The objective of this study was to evaluate the genetic structure between and within gene pools of a core collection of wild Phaseolus vulgaris L. using the technique of amplified restriction polymorphism (AFLP) analysis. DNA fingerprint patterns of 114 genotypes were analyzed by the NTSYS program. Major groups or gene pools were recognized in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
160
1
18

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(192 citation statements)
references
References 0 publications
13
160
1
18
Order By: Relevance
“…Typically, during domestication, important agronomic characters are selected which result in a genome-wide reduction of genetic diversity in the domesticates (Tanksley and McCouch 1997;Eyre-Walker et al 1998;Buckler et al 2001;Diamond 2002;Clark et al 2004;Papa et al 2007, Pozzi et al 2004Otero-Arnaiz et al 2005;Vasemagi et al 2005;Doebley et al 2006;Kilian et al 2007;Zhu et al 2007). Earlier studies in bean using DNA marker, protein and morphological variation, determined that domesticated landraces indeed contain a subset of the variability found in wild beans Debouck et al 1993;Kami et al 1995;Tohme et al 1996;Beebe et al 2001;Chacón et al 2005). Here we observed that the amount of variability/polymorphisms retained is similar to the diversity estimates found in wild types.…”
Section: A Model For Domestication In Common Beanmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, during domestication, important agronomic characters are selected which result in a genome-wide reduction of genetic diversity in the domesticates (Tanksley and McCouch 1997;Eyre-Walker et al 1998;Buckler et al 2001;Diamond 2002;Clark et al 2004;Papa et al 2007, Pozzi et al 2004Otero-Arnaiz et al 2005;Vasemagi et al 2005;Doebley et al 2006;Kilian et al 2007;Zhu et al 2007). Earlier studies in bean using DNA marker, protein and morphological variation, determined that domesticated landraces indeed contain a subset of the variability found in wild beans Debouck et al 1993;Kami et al 1995;Tohme et al 1996;Beebe et al 2001;Chacón et al 2005). Here we observed that the amount of variability/polymorphisms retained is similar to the diversity estimates found in wild types.…”
Section: A Model For Domestication In Common Beanmentioning
confidence: 99%
“…Two large gene pools of wild types were identified based on phaseolin seed protein variation Gepts 1990), DNA marker diversity (Becerra Velasquez and Gepts 1994;Sonnante et al 1994;Freyre et al 1996;Tohme et al 1996), morphology (Evans 1976;Gepts and Debouck 1991), isozymes (Koenig and Gepts 1989), mitochondrial DNA variation (Khairallah et al 1992) and amplified fragment length polymorphism (AFLP) (Rossi et al 2009) and short sequence repeats (SSR) ) marker data.…”
Section: Introductionmentioning
confidence: 99%
“…Common beans have exceptionally wide genetic variation among four gene pools and many races (Tohme et al 1996;Beebe et al 2001) two of which form the focus of sequencing work performed by Mamidi et al (2011). Reflecting this diversity, the CIAT maintains a primary gene bank with more than 36 000 accessions providing raw material for improving the crop using traditional breeding and molecular marker approaches.…”
Section: The Workhopmentioning
confidence: 99%
“…Polimorfismos de DNA amplificado ao acaso (RAPD), assim como outros marcadores de DNA, como RFLP (polimorfismos de comprimento de fragmentos de restrição) e AFLP (polimorfismos de comprimento de fragmentos amplificados) têm sido utilizados para medir a diversidade genética entre e dentro de espécies de microrganismos e plantas, incluindo o feijoeiro (Berkum et al, 1996;Tohme et al, 1996;Vasconcelos et al, 1996). Marcadores RAPD, pela sua simplicidade técnica e capacidade em detectar diferenças entre genótipos relacionados, são mais utilizados.…”
Section: Characterization Of the Genetic Diversity Of Common Beans Byunclassified